To Starve or Not to Starve the Beast? - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2010)
For thirty years prominent voices have advocated a policy of starving the beast cutting taxes to force government spending cuts. This paper analyzes the macroeconomic and welfare consequences of this policy using a two-country general equilibrium model. Under several strong assumptions the policy, if fully implemented, produces domestic output and welfare gains accompanied by losses elsewhere. But negative effects can easily arise in the presence of longer policy implementation lags, utility-enhancing government spending, and productive government capital. Overall, the analysis finds no support for the idea that starving the beast is a foolproof way towards higher output and welfare.